Problems of Criminal Sanctions for Narcotics Abuse: Comparative Study of National Crime and Islamic Crime - Mulyani, Melita; Hasuri (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
Narcotics abuse is one of the serious problems faced by the Indonesian state. Narcotics have many negative impacts. In Indonesia, the legal approach to dealing with this problem includes the application of criminal sanctions regulated in national law. However, in Indonesia as a country with the largest Muslim population in the world, the relevance and influence of Islamic law in regulating sanctions for narcotics abusers cannot be ignored. This study uses a qualitative method with a normative juridical approach. With the results of the research: criminal sanctions in Law no. 35/2009 include various forms of punishment, ranging from imprisonment to the death penalty, depending on the type and number of narcotics abused. In national law, more attention is paid to the human rights of narcotics violators. Meanwhile, heavier sanctions such as the death penalty are applied in Islamic law, aiming to provide a deterrent effect. Obstacles to handling and preventing narcotics abuse: weak coordination between agencies, limited rehabilitation facilities offered, lack of awareness, community, etc. Efforts to avoid narcotics abuse consist of pre-emptive efforts, preventive efforts, and repressive efforts. In addition, providing religious education from an early age to families, and selecting the use of media can also be done to prevent narcotics. The author's suggestion for the discussion of this research is the need for comprehensive cooperation between law enforcement officials and the community to achieve an orderly and prosperous life so that narcotics abuse in Indonesia can be resolved.